2016
DOI: 10.17265/2332-7839/2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Dehydration and Rehydration on Biomechanical Parameters of Elite Wrestling Techniques

Abstract: Abstract:The aim of this study was to investigate the effect of weight cutting and 18 hours rehydration in wrestlers' techniques performance. Methods: twenty-five men elite wrestlers participated in study, they randomly are divided into: group A (age of 18.38 ± 1.32 years, height 1.70 ± 0.04 m, weight 71.11 ± 11.80 kg) and group B (age of 21.00 ± 2.08 years, height 1.75 ± 0.04 m, weight 76.25 ± 12.55 kg). Body composition, biomechanical analysis were measure before dehydration, after weight cutting and after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…While RWL inherently involves dehydration processes, in professional combat sports such as MMA and boxing the competitive bout typically takes place ~ 30 to ~ 36 h after weigh-in (Burke et al 2021 ). This time-period may allow for rehydration and recovery of muscle glycogen (Burke et al 2021 ), but several studies have observed a residual negative impact on indices of performance even after ~ 16 to ~ 24 h of recovery (Oöpik et al 1996 ; Moghaddami et al 2016 ; Alves et al 2018 ; Yang et al 2018 ; Barley et al 2018b ; Kurylas et al 2019 ). Therefore, we also investigated the effect of RWL followed by ~ 24 to ~ 26 h of recovery in the form of a high carbohydrate diet and rehydration on body mass, hydration status, blood markers, and indices of performance.…”
Section: Introductionmentioning
confidence: 99%
“…While RWL inherently involves dehydration processes, in professional combat sports such as MMA and boxing the competitive bout typically takes place ~ 30 to ~ 36 h after weigh-in (Burke et al 2021 ). This time-period may allow for rehydration and recovery of muscle glycogen (Burke et al 2021 ), but several studies have observed a residual negative impact on indices of performance even after ~ 16 to ~ 24 h of recovery (Oöpik et al 1996 ; Moghaddami et al 2016 ; Alves et al 2018 ; Yang et al 2018 ; Barley et al 2018b ; Kurylas et al 2019 ). Therefore, we also investigated the effect of RWL followed by ~ 24 to ~ 26 h of recovery in the form of a high carbohydrate diet and rehydration on body mass, hydration status, blood markers, and indices of performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be that calorie restriction has greater impact on performance in BJJ than hypohydration (L. M. Burke et al, 2017). Notably, however, combat sport athlete's ad libitum rehydration methods do not appear to be effective (Alves et al, 2018;Moghaddami, Gerek, Karimiasl, & Nozohouri, 2016), suggesting that specific interventions may still be required for BJJ athletes who do perform dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…A uniform message is needed that stresses that this protocol must be considered as part of the old, unhealthy training style. Indeed, several studies have shown that these behaviors reduce the wrestler's physical and technical abilities to compete [30][31][32] . If changes in mentality are not achieved through education, it will be hard to change these unhealthy patterns because they are seen as an inherent part of the sport.…”
Section: Discussionmentioning
confidence: 99%